ANALISIS KOORDINASI CAMAT DALAM PELAKSANAAN PROGRAM NASIONAL PEMBERDAYAAN MASYARAKAT (PNPM) MANDIRI PERKOTAAN DI KECAMATAN KEDAWUNG KABUPATEN CIREBON (STUDI KASUS DI DESA KALIKOA) - Rico Darmawan; Achdi Halim; Hery Nariyah (Jurnal Ilmiah Publika, 2013)
The title of the study is: "Analysis of the Implementation Coordination Sub NationalCommunity Empowerment Program (PNPM) Mandiri Urban District Kedawung In CirebonRegency Village Kalikoa case study". This study reports the results of the background by thelack of support and guarantee the smooth implementation of PNPM Urban Village DistrictKalikoa Kedawung Cirebon regency. This study aimed to determine the extent of coordinationis done by the Head Kedawung and constraints. The research method used is descriptivequalitative approach to the research took place in the Village District Kalikoa KedawungCirebon regency. Meanwhile, the key informants (key informants) in this study is the VillageFacilitators (FASKEL). Data collection techniques used are literature studies, andobservation. The results showed that the coordination of the implementation of PNPM UrbanKedawung district level, the coordination of the 4 principles are 3 principles of coordinationthat have done well that coordination should be done from the very beginning stages, allpossibilities should be coordination meetings together, the differences in view should beexpressed openly and investigated in relation to the overall situation. While the principle hasnot been properly implemented the coordination is done continuously. This is due to lack ofcommunication and developmental factors Human Resources (HR) is still low.